Sposobin Remains. A Soviet Harmony Textbook’s Twisted Fate in China - Wai Ling Cheong; Ding Hong (Zeitschrift der Gesellschaft für Musiktheorie)
In 1937–38, Igor V. Sposobin and three co-authors at the Moscow Conservatory published Uchebnik garmonii [Harmony Textbook]. This was the first officially approved harmony textbook in the USSR, which came to be adopted as “the basic textbook for courses on harmony in the music schools of the Soviet Union” (Vladimir Protopopov, 1960). Characterized by its promulgation of the “scientifically based” theory of harmonic functions, this book was destined to be read by many more musicians in a foreign land. In 1955–56, Boris A. Arapov decreed at meetings held at the Central Conservatory of Music in China that the problem posed by the ethnicization of harmony should be solved by combining musical elements that are considered ethnically distinct with functional harmony. Wu Zuqiang, who had studied at the Moscow Conservatory in the 1950s before he headed the Central Conservatory in the 1980s, published a chapter from Uchebnik garmonii already in 1955. The first Chinese translation of the whole book by Zhu Shimin was then published in 1957–58. The book soon attained canonic status in China and has been used in virtually all Chinese music institutions up to the present day. It is listed in the entrance examination syllabi of selected conservatories and reputable music theorists have published model answers to the exercises it contains. This article investigates how the Chinese reception of Uchebnik garmonii diverges from the sources that had inspired Sposobin and his colleagues to compose it in the first place, and throws light on the far-reaching impacts and ramifications of Uchebnik garmonii in China. // 1937–38 publizierte Igor V. Sposobin gemeinsam mit drei Ko-Autoren Uchebnik garmonii [Lehrbuch der Harmonik] am Moskauer Konservatorium. Diese erste offiziell anerkannte Harmonielehre der UdSSR wurde zum “grundlegenden Lehrbuch für Harmonielehrekurse an Musikausbildungsstätten der Sowjetunion” (Vladimir Protopopov, 1960). Charakterisiert durch seine Verbreitung einer als “wissenschaftlich fundiert” erachteten Funktionstheorie, sollte das Buch noch von vielen weiteren Musiker*innen in einem anderen Land gelesen werden: Boris A. Arapov erklärte 1955–56 bei einer Konferenz am Zentralkonservatorium Beijing, dass das Problem einer “Ethnisierung” von Harmonik gelöst werden solle, indem musikalische Elemente, die als ethnisch different aufgefasst werden, mit Funktionsharmonik kombiniert werden. Wu Zuqiang, der in den 1950er Jahren am Moskauer Konservatorium studierte und in den 1980er Jahren dann Präsident des Beijinger Zentralkonservatoriums wurde, legte bereits 1955 die Übersetzung eines Kapitels aus Uchebnik garmonii vor, worauf 1957–58 dann die erste vollständige Übersetzung von Zhu Shimin folgte. Das Lehrbuch erhielt rasch einen kanonischen Status in China und ist in nahezu allen Musikinstitutionen des Landes bis zum heutigen Tag in Verwendung. Es ist in den Anforderungen zur Zulassungsprüfung und den Lehrplänen einiger Konservatorien angeführt, und angesehene Musiktheoretiker haben Modelllösungen zu den Übungen des Buchs veröffentlicht. Dieser Beitrag untersucht wie die chinesische Rezeption von Uchebnik garmonii sich von den Quellen entfernte, die Sposobin und seine Kollegen ursprünglich motiviert hatten, das Buch zu verfassen. Dadurch wird deutlich, welche weitreichenden und unvorhersehbaren Auswirkungen Uchebnik garmonii in China mit sich brachte.